My friends : a novel [compact disc, unabridged] - Backman, Fredrik, 1981- (Simon & Schuster, 2025)
Most people don't even notice them - three tiny figures sitting at the end of a long pier in the corner of one of the most famous paintings in the world. Most people think it's just a depiction of the sea. But Louisa, an aspiring artist herself, knows otherwise, and she is determined to find out the story of these three enigmatic figures.